An improved DV-Hop localization method in Wireless Sensor Networks - Wenqi Yu; Hao Li (2012 IEEE International Conference on Computer Science and Automation Engineering, 2012)
Localization is one of the most important issues in Wireless Sensor Networks (WSNs), especially for the applications requiring the accurate position of the sensed information. The traditional DV-Hop method can be simply implemented in real wireless sensor networks without any range measurement tools, but it has bad localization accuracy. To overcome the shortcoming of the traditional DV-Hop method on localization accuracy, an improved DV-Hop localization method is proposed in this paper. The proposed method is derived from DV-Hop method, and adds correction to the distance between anchor nodes and unknown nodes to improve localization accuracy without increasing hardware cost for sensor nodes. Simulation results show that the localization accuracy of the improved DV-Hop method outweighs significantly the traditional DV-Hop method.